Aeromonas-Associated Infections in Developing Countries - Khalifa Sifaw Ghenghesh; Salwa F. Ahmed; Rania Abdel El-Khalek; Atef Al-Gendy; John Klena (Journal of Infection in Developing Countries)
Although their role in gastroenteritis is controversial, Aeromonas species are recognized as etiological agents of a wide spectrum of diseases in man and animals. In developing countries, potentially pathogenic Aeromonas sp. are very common in drinking water and in different types of foods, particularly seafood. Several food-borne and water-borne outbreaks as well nosocomial outbreaks associated with aeromonads have been reported. Significant association of Aeromonas sp. with diarrhoea in children has been reported from several countries. These organisms are important causes of skin and soft-tissue infections and aspiration pneumonia following contact with water and after floods. High incidence of antimicrobial resistance, including to third-generation cephalosporins and the fluoroquinolones, is found among Aeromonas sp. isolated from clinical sources in some developing countries in Asia. Isolating and identifying Aeromonas sp. to genus level is simple and requires resources that are available in most microbiology laboratories for processing common enteric bacteria. The present review will cover the epidemiology, clinical syndromes, low-cost diagnostic methods, and antimicrobial resistance and treatment of Aeromonas infections in developing countries.